MODEL PERILAKU KESEHATAN KELUARGA PENERIMA JAMKESMAS - Sandu Siyoto (STRADA : Jurnal Ilmiah Kesehatan, 2012)
To prevent the worse health condition especially for poor society because of monetary crises since 1997, the government launched Public Health Assurance or Jamkesmas (Jaminan Kesehatan Masyarakat). This program gave health service freely to the poor society at the choosen health service places. However, the advantages of this program were still low. It was around 39.8% (Public Health Department, 2011). Beside, based on monitoring, poor society behavior didn’t support this program also. They showed unhealthy behavior. The goal of this research was to develope health behavior model of Jamkesmas recipients in Kediri City East Java, also the factors which influenced them. This research was Observation Research with crosssectional design. There were 270 respondents taken by using two stage cluster sampling technique. The data were gathered by valid and reliable questionnaire. After that, the data were analyzed descriptively by using binnary logistic regression statistic analysis to test model feasibility and regression coefficient. The results of research showed that ost of Jamkesmas recipients had unhealthy behavior, many sick complaints and worries, ut they didn’t go to the health services which were refered. This research also found that ck complaint level (need) was influenced by dwelling ownership status, family status, he th value and knowledge about disease and Jamkesmas at predisposing factors, also sp ding money for food at enabling factor, and health behavior practice. Health behavior practice of Jamkesi s recipients and their family were influenced by education level, health value at predispo ng factor and spending money for cigarette and perception toward health service at abling factor. As well as health service utilization was influenced by worry level of t e sickness that they felt and spending money for food.